Overcoming secondary stress in medical and nursing practice - Wicks, Robert J. (Oxford University Press, 2006)
Physicians, nurses, and allied health professionals working in today's health care settings must be prepared to offer support in dangerous times despite staffing shortages, financial pressures, and complex legal requirements. Overcoming Stress in Medical and Nursing Practice: A Guide to Professional Resilience and Personal Well-Being is a concise guide for all medical professionals who face these demands. This book: ã Provides critical information about the dangers of compassion fatigue/burnout and vicarious post-traumatic stress disorder in health care settings ã Introduces a newly-developed "Medical-Nursing Professional